NX 12 for beginners (Tutorial Books, 2018)
'NX 12 For Beginners' introduces you to the basics of NX 12 by using step-by-step instructions. You begin with a brief introduction to NX 12 and the user interface, ribbon, environments, commands, and various options. Within a short time, you will learn to create 2D sketches that form the basis for 3D models.